Gelykenisse in konteks: Aantekeninge oor Matteus 24:45–25:30 - Botha, P. J. J. (Verbum et ecclesia, 1996)
Parables in conte:d: some comments on Matthew 24:45-25:30 The three parables in Matthew 24:45-25:30 are usually read as advice to the church on how to behave while waiting for the return of the Lord. An alternative reading is proposed in this article: Matthew discusses the relationship between various Jewish groups, explaining who the disciples of the Kingdom are and why fonnative Judaism, competing for the allegiance of Jews of the late first century, is not a viable option for the future of Israel's inheritance.